If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + -4) = -6 Reorder the terms: 3(-4 + 3x) = -6 (-4 * 3 + 3x * 3) = -6 (-12 + 9x) = -6 Solving -12 + 9x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 9x = -6 + 12 Combine like terms: -12 + 12 = 0 0 + 9x = -6 + 12 9x = -6 + 12 Combine like terms: -6 + 12 = 6 9x = 6 Divide each side by '9'. x = 0.6666666667 Simplifying x = 0.6666666667
| 2/3x-6=4 | | 5x+61=8x-14 | | -4(3x+5)=5(-2x-3) | | x/-2-8=22 | | 6x^2-13x-11=0 | | -4-5x=21 | | (x+3)(x-4)=o | | 30x+50y=240 | | 29=b/4+15 | | 5b+1/2b+2b+1/3b | | (7/8)x+1=(5/8)x | | -17+t/5=3 | | 3x/2-4=21 | | x^3-3x^2-8x+12=0 | | 10+11x=40+x | | 15n^2+17n-4=0 | | 5x+37=12x-33 | | 5x+37=12x-33 | | 5x+37=12x-33 | | 5x+37=12x-33 | | 5(2y+1)=3(4-5y) | | 9+-8x=40-15x | | 3(2x-5)=-1 | | 8x-29=3x+1 | | 3x-2=10-3x | | 5+3(-2x+2)=6-4(x+1) | | 9-8x=34x+23 | | 15x-7=9+7x | | 8(9+b)-4b= | | 3r+17-2r+6= | | v^2-16v-20=-5 | | -10=5g |